2009
DOI: 10.2118/126129-pa
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on the Geomechanical Stability of Hydrate-Bearing Sediments

Abstract: The thermal and mechanical loading of oceanic hydrate-bearing sediments (HBS) can result in hydrate dissociation and a significant pressure increase with potentially adverse consequences on the integrity and stability of the wellbore assembly, the HBS, and the bounding formations. The perception of HBS instability, coupled with insufficient knowledge of their geomechanical behavior and the absence of predictive capabilities, has resulted in a strategy of avoidance of HBS when locating offshore production platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 22 publications
1
96
0
Order By: Relevance
“…Earlier studies (Rutqvist and Moridis 2009) have shown that gas production from such deposits is often accompanied by significant subsidence, with potentially important consequences for well and reservoir stability, as well as for the evolution of the sediment permeability. Because this study indicated the generally low production potential of CH (a determination that does not encourage their further evaluation when more promising hydrate deposits are available), the issue of geomechanical response of CHs was not pursued in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies (Rutqvist and Moridis 2009) have shown that gas production from such deposits is often accompanied by significant subsidence, with potentially important consequences for well and reservoir stability, as well as for the evolution of the sediment permeability. Because this study indicated the generally low production potential of CH (a determination that does not encourage their further evaluation when more promising hydrate deposits are available), the issue of geomechanical response of CHs was not pursued in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, TOUGH + HYDRATE 62 software was employed to address this issue because the software was generally used to simulate gas recovery from hydrate reservoirs in marine and permafrost regions, 27,28,30,[63][64][65] The geomechanical response was not considered because the influence of effective stress variation on the sediment and fracture properties in GHBS at this site during depressurization is currently unclear, even though the coupled thermo-hydro-mechanical model was proposed and used to perform the coupling processes during drilling and gas recovery. 25,29,[66][67][68][69][70][71][72] However, the assigned permeability of fractures takes the influence of the effective stress into account. The latter means that the value adopted is the experimental measurement in other sediments after which the bottom hole pressure remains constant after initially decreasing (i.e., the assigned fracture permeability is measured at the corresponding effective confining pressure condition).…”
Section: Numerical Simulation Codementioning
confidence: 99%
“…This class of deformation, which is caused by changes in stress states, whether volume contraction or expansion, can be assessed based on the material stiffness. Many of reservoir-scale geomechanics simulators, including those presented by the Lawrence Berkeley National Laboratory (LBNL) group [40][41][42], by the Korea Advanced Institute of Science and Technology (KAIST) group [39,43], and by the Cambridge University group [44][45][46], adopt elastoplasticity to model sediment deformation behaviors. Thereby, one of the elastic moduli (typically Young's modulus or bulk Energies 2016, 9, 775 15 of 23 modulus), Poisson's ratio ν, and strength parameters (cohesion and friction angle, if Mohr-Coulomb yield criterion used) for material yielding are typically used as input parameters for describing elasto-plastic behavior.…”
Section: Stress-and Strain-dependent Young's Modulusmentioning
confidence: 99%
“…Accordingly, Young's modulus of hydrate-bearing sediments is assumed based on linear interpolation between the values at two different hydrate saturations-typically, one for hydrate-free sediment and the other for a certain hydrate saturation (e.g., [40][41][42][43][44][45][46]62]). On the other hand, a logarithmic increase of the secant Young's modulus of hydrate-bearing sediments has been also observed with increasing hydrate saturation by Yoneda et al [25].…”
Section: Geomechanical Propertiesmentioning
confidence: 99%